Revised middle Eocene - upper Oligocene calcareous nannofossil biozonation for the Southern Ocean - FIORONI, Chiara; Villa G.; Persico D.; Wise S. W.; Pea L. (Revue de Micropaléontologie, 2012)
Calcareous Nannofossils are widely utilized in biostratigraphic studies of Cenozoic sediments.In recent years large datasets have been acquired, and several bioevents showed to be unreliable whencorrelated over distant areas. New biostratigraphic investigations of middle Eocene-upper Oligocenedeep-sea cores have highlighted problem areas in the currently used calcareous nannofossil zonalschemes for the Southern Ocean for this time interval. Quantitative analysis on sediments from sevensites from this area, characterized by abundant, diverse, and moderately to well-preserved nannofloralassemblages, have enabled a revision of the existing zonation for the Southern Ocean, and thedevelopment of a high-resolution zonal scheme for the middle Eocene-upper Oligocene. Eleven zonesand six subzones are introduced or emended to replace the ten zones and two subzones of the Wei andWise (1990a) and Wei and Thierstein (1991) zonations, with the identification of several newbiohorizons. New age calibrations are provided improving regional correlations and evaluating thereliability of the identified events for supraregional correlations. Comparisons are made between theproposed zonation and the existing schemes, both on nannofossils from different geographic areas, andon foraminifers from southern high latitude.